P3.74 Antimicrobial susceptibility profiles of species of ureaplasma parvum and ureaplasma urealyticum isolated in buenos aires, argentina. (8th July 2017) - Bardossy, ES; Vacchino, M; Díaz, M; Galarza, P
Abstract : Introduction: Ureaplasma parvum (Up) and Ureaplasma urealyticum (Uu) are small cell wall-lacking bacteria that colonise humans, but can cause disease among pregnant women, neonates, sexually active individuals and immunocompromised. They are naturally resistant to several antibiotics, and treatment relies in fluoroquinolones, tetracyclines, macrolides and chloramphenicol. Acquired resistance has been described in other countries, but data on the antimicrobial susceptibility in Argentina are lacking. We aimed to describe the antimicrobial susceptibility profiles of Up/Uu isolates recovered from clinical samples between 2004 and 2016 in Buenos Aires, Argentina. Methods: A total of 89 isolates from clinical samples originally submitted to the STI National Reference Laboratory for diagnosis between 2004 and 2016 were examined. Isolates were grown in conventional culture mediums (broth and agar) and species confirmed by PCR. Antimicrobial susceptibility tests were done by broth microdilution method following CLSI. Results: Of the 89 isolates analysed, two showed resistance to levofloxacin (MIC 4 ug/ml) and one was resistant to tetracycline (MIC 4 ug/ml), giving a prevalence of resistance of 2.2% (CI 0.6%–7.8%) and 1.1% (CI 0.2%–6.1%), respectively. All isolates were susceptible to erythromycin and azithromycin. MIC50, MIC90 and MICranges were 1, 2, 0.25–4 for levofloxacin; 0.5, 1, 0.06–4 for tetracycline; 2, 4, 0.25–4 for erythromycin; and 2, 4, 0.25–8 for azithromycin. Levofloxacin and tetracycline MIC values were higher for Uu (n=18, 20%) than for Up (n=71, 80%), but no differences were observed among macrolides. No MICs differences were observed between 2004–2009 strains (n=49, 55%) and 2010–2016 (n=40, 45%) isolates. Finally, no coresistant strains were identified. Conclusion: To our knowledge, this is the first study analysing the susceptibility patterns of species of ureaplasma in Argentina following CLSI recommendations. We found low resistance rates to levofloxacin and tetracycline, and no resistance to macrolides, but continue surveillance is needed to detect the emergence of resistant strains and to characterise the molecular determinants of these findings.